(untitled) (Development Engineering Conferences Center Articles Database, 2025)
The bullwhip effect, as one of the major challenges in supply chain management, amplifies demand fluctuations at upstream levels and disrupts coordination and operational efficiency. This study develops a hybrid framework based on multi-criteria decision-making (MCDM) methods to select optimal suppliers for Haierplast Factory engaged in the production of primary plastic components for household appliances and to mitigate the bullwhip effect. the research integrates the Fuzzy Analytic Hierarchy Process (Fuzzy AHP), the Decision-Making Trial and Evaluation Laboratory (DEMATEL), and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The framework is further enhanced through the incorporation of fuzzy logic, dynamic analysis, and novel criteria, namely environmental sustainability and operational flexibility. Four real-world suppliers (Jam Petrochemical, Baspar Shimi, Marun Petrochemical, and Pouya Polymer) are evaluated against criteria including delivery time, operating cost, service quality, operational flexibility, and environmental sustainability. The findings reveal that Baspar Shimi is the most suitable supplier due to its superior performance in delivery time and flexibility. Simulation and sensitivity analysis confirm a 15% reduction in demand deviation. By offering a generalizable approach, this framework contributes to the supply chain management literature and provides a strategic tool for manufacturing industries operating in similar contexts.